Circumstancial unconstitutionality and the Direct Action of Unconstitutionality n. 4.068 (Research, Society and Development, 2021)
The circumstantial unconstitutionality thesis presented in the Direct Action of Unconstitutionality n. 4068 / DF meant the possibility of a new form of constitutionality control. The theme is part of the analysis of the feasibility of declaring momentary unconstitutionality due to exceptional factual circumstances and not exactly the content of the standard. Therefore, the circumstantial unconstitutionality and its foundations was examined, addressing the criticisms directed at the new thesis. The discussion involves the thesis raised in the Direct Action of Unconstitutionality promoted by the Federal Council of the Brazilian Lawyers (CFOAB). The process refers that despite the circumstantial unconstitutionality of the contested norm that law deserves to be preserved. For the research it was uses the analytical-descriptive method, bibliographic research to scientific articles, books and Jurisprudence. Finally concludes the decision of the Federal Supreme Court did not faced the thesis of circumstantial unconstitutionality, because it would imply invading the discretion of the administrator implying in violation of the principle of separations of powers.